Deteksi Keberadaan Liberobacter asiaticum Pada Tanaman Jeruk Yang Terserang Citrus Vein Phloem Degeneration (CVPD) Dengan Gejala Parsial - VANI SILVANA; I NYOMAN WIJAYA; I GEDE PUTU WIRAWAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Detection Of The Existence of Liberobacter Asiaticum in Citrus Stricken with Sympthoms of Partial CVPD Citrus Vein Phloem Degeneration (CVPD) is a major disease of citrus caused by Gram-negative bacteria Liberobacter asiaticum. The symptoms of the disease were varied due to many factors such as type of pathogenic races of the pathogen, types of citrus trees, and the presence or spread of plant pathogens in the plant. This study aims to detect the existence or distribution of pathogens of CVPD in citrus plant with partial symptoms. Samples were taken from the bone leaves, bark twigs, bark of branches and bark of stem whether symptomatic or non symptomatic. Sampling was carried out in Plaga village, Badung Regency, Bali and analysis of polymerase chain reaction (PCR) was conducted in UPT Lab Genetics Resources and Molecular Biology, Udayana University. The results of this study indicate that the amplified DNA of 1160 bp was found in the first plant that was  symptomatic leaf, twig bark of leaf symptomatic and non symptomatic leaves. While on the second sample of citrus plants, DNA fragments were found on the leaves and symptomatic leaf and non symptomatic, and they were not found in other parts of plant, namely twig bark, branch bark, bark of stem. These results indicate that in citrus with partial symptoms the distribution of pathogens L. asiaticumwere only partial in plant.